Effect of Intravenous Lidocaine Infusion on Propofol Dose and Perioperative Pain During Moderate Sedation-Analgesia for Hysteroscopy: A Randomized Controlled Trial - Yang F; Wang J; Zhang H; Zhang Y; Yang W; Gao R; Yu J; Chen X; Ma H (Drug Design, Development and Therapy)
Fan Yang,1,* Jie Wang,1,2,* Huiwen Zhang,1 Yonghai Zhang,1 Wanji Yang,1 Ran Gao,1 Jingfang Yu,1 Xuexin Chen,1 Hanxiang Ma1 1Department of Anesthesiology, General Hospital of Ningxia Medical University, Yinchuan, 75004, People’s Republic of China; 2Department of Anesthesiology, Yan’an Hospital Affiliated to Kunming Medical University, Kunming, 650051, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuexin Chen; Hanxiang Ma, Department of Anesthesiology, General Hospital of Ningxia Medical University, No. 804 Shengli South Street, Yinchuan, 750004, People’s Republic of China, Email Chenxuexin2637@163.com; mahanxiang@hotmail.comPurpose: In China, the majority of hysteroscopic procedures require moderate sedation and analgesia. The efficacy of intravenous lidocaine in reducing the need for sedatives and alleviating perioperative pain during hysteroscopy remains equivocal. This study aims to determine whether the intravenous administration of lidocaine can reduce the required dose of propofol and enhance perioperative pain management.Patients and Methods: We conducted a prospective, single-center, double-blind randomized controlled trial involving patients with ASA I–II undergoing hysteroscopy. Forty patients were randomly assigned in a 1:1 ratio to either receive an intravenous bolus dose of 1.5 mg/kg lidocaine, followed by a continuous intravenous infusion at 4 mg/kg/h until the conclusion of the procedure, or an equivalent volume of normal saline. Propofol was then titrated to maintain a MOAA/S score of ≤ 2.Results: Compared with the control group, the lidocaine group showed a 13.8% decrease in the total dose of propofol (140.0[120.0, 155.0] mg vs 162.5[140.0, 197.5] mg), which was statistically significant (P = 0.014). The induction dose of propofol was 1.37 (1.29, 1.56) mg/kg in the lidocaine group and 1.61 (1.48, 1.94) mg/kg in the control group, respectively (P = 0.001). However, no significant differences were observed between the groups regarding the supplemental dose of propofol (P = 0.062), the number of involuntary movements during hysteroscopy (P = 0.384), or postoperative pain scores (T0: P = 0.628; T1: P = 0.886; T2: P = 0.711). Additionally, the incidence of intraoperative hypoxia (P = 1.000) and fatigue scores (T0: P = 0.878; T1: P = 0.401; T2: P = 0.056) between the two groups were not statistically significant.Conclusion: Intravenous lidocaine reduces the dose requirements of propofol during the induction phase of anesthesia. However, it does not have a significant influence on alleviating intraoperative and postoperative pain during hysteroscopic procedures.Keywords: analgesia, hysteroscopy, lidocaine, propofol, sedation